(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the viability of in vitro produced embryos (IVPE) bovine at different developmental stages, maintained at 36ºC at different transport times. On the seventh day of in vitro culture, grade I and II embryos at early blastocyst, blastocyst, and expanded blastocyst stages were selected, packaged and randomly distributed to three transport times in a portable incubator at 36°C: 6, 9 and 12 hours. After the treatment time, embryos were re-cultured in culture medium for 72 hours and evaluated for quality and development. Hatching and degeneration rate data were analyzed by Chi-square test. Embryos packaged at the expanded blastocyst stage showed higher hatching rates and lower degeneration rates. Embryos packaged at the expanded blastocyst stage showed higher viability compared to those at early blastocyst, regardless of transport time, and blastocysts transported for 6 and 9 hours.